Conceptual Process Integration of a Machine Learning Applications with AutomationML and OPC UA Fakultät - Julian Bonas (2022)
The idea of Industry 4.0 pursues the vision of production systems whose components are fully interconnected and integrated into their environment. This enables these systems to share their information and capabilities. In this thesis it shall be illustrated how these ideas can also be applied to pure software components. A machine learning application using OPC UA and AutomationML is described and a concept for the integration into an automation process is presented.
Keywords: Industrie 4.0; OPC UA; AutomationML; Machine Learning; Automation; Skill-Basierte Prozesssteuerung